An exploratory study of uses of ‘urban security’ and ‘urban safety’ in international urban studies literature - Tulumello, Simone (2017)
The article explores systematically, albeit preliminarily, the way the concepts of security and safety are employed in scholarly urban studies literature about crime (and the prevention of it). It employs network analysis on author keywords, complemented with text analysis of abstracts, over sets of bibliographic information retrieved from Web of Science. Using a critical interpretative analysis of findings, and looking at the geography of main scholarly communities in this field, the article highlights differences (especially at the operational level) and commonalities (especially at the conceptual level) in the way scholars understand urban security and urban safety. Concluding that this field of study is dominated by operational, evidence-based approaches, the article advocates for a renewed critical engagement of scholarship in this field, through studies that would shift their attention from technical ‘solutions’ to the ‘problems’ that lead societies to demand security/safety.